Kreativitas Guru Dalam Membuat Alat Permainan Edukatif Dari Barang Bekas - Mukti Wigati; Novan Ardy Wiyani (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2020)
The main problem that is the focus of this research is the process of making educational toys with used goods in TK IT Al Fattaah Sumampir Purwokerto. This study aims to describe TK IT Al-Fattaah Sumampir Purwokerto in the manufacture of educational game tools with used goods. This research is a descriptive qualitative research. The method in collecting data that I use is observation, interview and documentation. Whereas in data analysis using the method of reducing data, presenting data, and inferring data. The results of this study indicate that TK IT Al-Fattaah Sumampir Purwokerto has tried to make their own educational game tools with used goods. In making educational game tools there are three stages, namely the determination of tools and materials, the manufacturing process, the use of educational games tools with used goods, and evaluation process to educational games Keywords: educational games, used item, creativityReferensiAde Husnul Mawadah. (2018). Pemanfaatan Big Book Sebagai Media Literasi Anak Usia Dini. Jurnal as-Sibyan UIN Banten, 3(1), 57–72.Dista, F. N. (2019). Penerapan Pendekatan Saintifik dalam Mengembangkan Berpikir logis Anak Usia 5-6 Tahun di RA Takrimah Tungkop Aceh Besar. AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 5(2), 217–236. Dwi Nurjannah. (2018). Peningkatan Motorik Halus Anak Melalui Kegiatan Bermain Papercraft (Penelitian Tindakan di TK Alam Rizkia, Depok). Jurnal al Athfal UIN Sunan Kalijaga Yogyakarta, 4(2), 149–160. Hamzah B.Uno dan Nurdin Mohamad. (2013). Belajar dengan Pendekatan PAIKEM. Bumi Aksara.Hasanah, U. (2019). Penggunaan Alat Permainan Edukatif (Ape) Pada Taman Kanak-Kanak Se-Kota Metro. AWLADY : Jurnal Pendidikan Anak, 5(1), 20. Huliyah, M. (2016). Pengembangan Daya Seni Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 149–164. Imroatun, I. (2016). Bermain Sebagai Metode Pembelajaran Utama Anak Raudhatul Athfal. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 40–48. Mukhlis, A. (2019). Dominasi Guru Perempuan dalam Pendidikan Anak Usia Dini: Persepsi Stakeholder. AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 5(2), 117–134. Novan Ardy Wiyani. (2014). Psikologi Perkembangan Anak Usia Dini: Panduan bagi Orang Tua dan Pendidik PAUD dalam Memahami serta Mendidik Anak Usia Dini. Gavamedia.Novan Ardy Wiyani. (2015). Manajemen PAUD Bermutu: Konsep dan Praktik MMT di KB. Gavamedia.Novan Ardy Wiyani dan Barnawi. (2012). Format PAUD. Ar-Ruzz Media.Novi Mulyani. (2019). Pengembangan Kreativitas Anak Usia Dini Melalui Bermain Gerak Dan Lagu Di Tk Negeri Pembina Kabupaten Purbalingga. Jurnal as-Sibyan UIN Banten, 4(1), 13–23.Novita, A., & Muqowim, M. (2019). Inovasi Guru dalam Metode Pembelajaran Berhitung untuk Menstimulasi Kecerdasan Logis-Matematis di TK Kalyca Montessori School Yogyakarta. AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 5(1), 21–36. Nuryati dan Nuni Yuniawati. (2019). Peningkatan Kreativitas Pada Anak Usia Dini Kelas Sd Awal Usia 6-8 Tahun Melalui Metode Praktikum Membatik. Jurnal as-Sibyan UIN Banten, 4(1), 1–11.Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60.Ramli, S. A., & Muhajir, H. M. (2019). Efektivitas Media Celemek Ilmu Terhadap Pengembangan Aritmatika Anak Umur 5-6 Tahun Di Taman Kanak-Kanak Kota Palopo. AWLADY : Jurnal Pendidikan Anak, 5(2), 146. Ridwan Abdullah Sani. (2013). Pembelajaran SAINTIFIK untuk Implementasi Kurikulum 2013. Bumi Aksara.Riris Eka Setiani. (2019). Pemanfaatan Permainan Tradisional Dalam Penanaman Nilai-Nilai Kebangsaan Di Tk Negeri Pembina 2 Purwokerto. Jurnal as-Sibyan UIN Banten, 4(1), 39–52.Sari, D. P. (2019). Pembelajaran Huruf Hijaiyyah Pada Sentra Agama Di Taman Kanak-Kanak Tunas 1001 Takengon Aceh Tengah. AWLADY : Jurnal Pendidikan Anak, 5(2), 130. Saripudin, A. (2019). Kompetensi Guru Pendamping Paud Dalam Memenuhi Standar Layanan Paud Non Formal Di Kabupaten Tasikmalaya. AWLADY : Jurnal Pendidikan Anak, 5(2), 63. Ulfa, M. (2019). Pembelajaran PAKEM Berbasis Media Audio Visual Gerak dalam Melatih Konsentrasi Belajar Anak di TPA Sahabat Hati Pontianak. AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 5(1), 53–68. Warni Djuwita dan Mohammad Fakhri. (2019). Pengaruh Permainan Tradisional Dalam Mengembangkan Kecerdasan Jamak Anak Usia Dini Pada PAUD Di Kota Mataram. Jurnal as-Sibyan UIN Banten, 4(2), 87–102.